Problems Solving of Credit with Liability Which Owner Has Died - Hepy Hapsari Hapsari; Sukarmi Sukarmi (Sultan Agung Notary Law Review, 2020)
The purpose of this study was to: 1) To identify and analyze the implementation of the settlement of non-performing credits are collateralized with mortgage collateral while the owner died. 2) To identify and analyze the role of the Notary of the Installation Encumbrance with Certificate Name Properties that have made the process dies down to the Expert Heir based Justice. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analysis method. Based on the results of data analysis concluded that: 1) the implementation of the settlement of non-performing credits are collateralized with mortgage collateral while the owner died. 2) the role of the Notary of the Installation Encumbrance with Certificate Name Properties that have made the process dies down to the Expert Heir based Justice.